A história da Ciência, as “duas culturas” e a interdisciplinaridade - Stefanovits, Angelo (2016)
The History of Science was idealized, in the 19th century, by Auguste Comte, who saw in that new discipline a way to counter specialization and knowledge dispersion. It was institutionalized, in the earlier decades of the 20th century, by George Sarton, a Belgium scientist and humanist who settled in the United States when the First World War broke out. Conducting his research nearly one century after the French philosopher, Sarton pursued, similarly to Comte, the elaboration of a History of Science, and not a History of the Sciences, in contrast to the trend of most journals published in his time, which were devoted to writing the history of particular sciences. Sarton conceived the History of Science as an interdisciplinary enterprise responsible for establishing a connection between the natural sciences and the humanities, which would later be referred to as the “two cultures.” From the 1970s, reflections on the concept of interdisciplinarity emerged in several areas besides the History of Science and touched upon some of its themes, among which dispersion of knowledge and the way to interrelate different disciplines and areas of study. The OECD (Organization for Economic Cooperation and Development) and Unesco (United Nations Educational, Scientific and Cultural Organization) were two of the major agencies that participated in discussions about interdisciplinarity, through publication of academic journals that gained worldwide impact, mainly in the field of Education. Thus, this thesis seeks to better understand such process of discontinuities and permanencies that, since the first decades of the 20th century, has promoted interdisciplinarity. It also seeks to offer some indications on its latest problems and solutions, including in Brazil